Effect of Nano Particle Deposition on Mechanical Properties of Friction Stir Welded Dissimilar Aluminium Alloys by Taguchi Technique - Reddy, Baridula Ravinder; Ramgopal , Varma Ramaraju; Abdullah, Ibrahim; C. K. M., Faizal (Springer, 2016)
Improving the mechanical properties while joining of dissimilar alloys by FSW has been a choice of research during the past decade. Hence, an attempt has been made in the present research to join dissimilar Al alloys (AA5052 and AA6063) by addition of Copper nanoparticles in the weld joint. A 5T NC FSW machine has been employed to perform the desired task. To achieve optimum values of the process parameters, an optimization study has been carried out using Taguchi technique. The results obtained from the optimization studies and experimental investigations match very well proving the efficacy of the study. The results from the investigation show an improvement in mechanical properties when Cu nanoparticles are deposited which are further supported by microstructure and EDX analysis.